Development of a high-throughput cell-based reporter assay for screening JAK3 inhibitors - Yin, Chang-Hong (2011)
JAK3 has become an ideal target for the therapeutic treatment of immune-related diseases, as well as for the prevention of organ allograft rejection. A number of JAK3 inhibitors have been identified by in vitro biochemical enzymatic assays, but the majority display significant off-target effects on JAK2. Therefore, there is an urgent need to develop new experimental approaches to identify compounds that specifically inhibit JAK3. Here, we showed that in 32D/IL-2Rβ cells, STAT5 becomes phosphorylated by IL-3/JAK2- or IL-2/JAK3-dependent pathway. Importantly, the selective JAK3 inhibitor CP-690,550 blocked the phosphorylation as well as the nuclear translocation of STAT5 following treatment of cells with IL-2, but not with IL-3. In an attempt to use the cells for large-scale chemical screens to identify JAK3 inhibitors, we established a cell line 32D/IL-2Rβ/6×STAT5 stably expressing a well-characterized STAT5 reporter gene. Treatment of this cell line with IL-2 or IL-3 dramatically increased the reporter activity in a high-throughput format. As expected, JAK3 inhibitors, CP-690,550 and JAK3 inhibitor VI, selectively inhibited the activity of the 6×STAT5 reporter following treatment with IL-2. By contrast, the pan-JAK inhibitor Curcumin non-selectively inhibited the activity of this reporter following treatment with either IL-2 or IL-3. Thus, this study indicates that our STAT5 reporter cell line can be used as an efficacious cellular model for chemical screens to identify low-molecular-weight inhibitors specific for JAK3.